Concept and development of a unified ontology for generating test and use‐case catalogues for assisted and automated vehicle guidance. Issue 3 (1st May 2014) - Geyer, Sebastian; Baltzer, Marcel; Franz, Benjamin; Hakuli, Stephan; Kauer, Michaela; Kienle, Martin; Meier, Sonja; Weißgerber, Thomas; Bengler, Klaus; Bruder, Ralph; Flemisch, Frank; Winner, Hermann
Abstract : Activities in the field of automated driving have produced a variety of development tools and methodologies over the past decades. The requirements the systems have to fulfil and thus also the development guidelines are often documented in different kinds of catalogues (use‐case catalogues, situation catalogues, scenario catalogues etc.). These catalogues cannot be directly applied for the development of partially and highly automated vehicle guidance concepts like conduct‐by‐wire (CbW) or H‐mode. One reason is that up to now, no consistent terminology known to the authors yet exists for vehicle automation within the community. Moreover, as the aim of the two project groups CbW and H‐mode is to make a comprehensive feasibility assessment of cooperative vehicle guidance, all interacting components of the overall system as well as all potential driving conditions a cooperative vehicle guidance system might have to cope with have to be analysed. This article focuses on two aspects. The first is a metaphor‐based terminology discussion leading to a proposal for a fundamental ontology. The second aspect is an outlook on the different catalogues that use the new terminology and that have been developed. The methodology introduced here is a fundamental contribution towards simplifying communication and the exchange of findings.